Fighting Bisphenol A-Induced Male Infertility: The Power of Antioxidants - Joana Santiago; Joana V. Silva; Manuel A. S. Santos; Margarida Fardilha (MDPI AG, 2021)
Bisphenol A (BPA), a well-known endocrine disruptor present in epoxy resins and polycarbonate plastics, negatively disturbs the male reproductive system affecting male fertility. In vivo studies showed that BPA exposure has deleterious effects on spermatogenesis by disturbing the hypothalamic-pituitary-gonadal axis and inducing oxidative stress in testis. This compound seems to disrupt hormone signalling even at low concentrations, modifying the levels of inhibin B, oestradiol, and testosterone. The adverse effects on seminal parameters are mainly supported by studies based on urinary BPA concentration, showing a negative association between BPA levels and sperm concentration, motility, and sperm DNA damage. Recent studies explored potential approaches to treat or prevent BPA-induced testicular toxicity and male infertility. Since the effect of BPA on testicular cells and spermatozoa is associated with an increased production of reactive oxygen species, most of the pharmacological approaches are based on the use of natural or synthetic antioxidants. In this review, we briefly describe the effects of BPA on male reproductive health and discuss the use of antioxidants to prevent or revert the BPA-induced toxicity and infertility in men.